Management and Evaluation of Communication and Coordination Practices among Multi Stakeholders in Complex Engineering Projects in Pakistan - Kamran Siddique; M. Zeeshan Ahad; Wasim Ud Din (European Scientific Journal, ESJ, 2019)
The aim of this study is to investigate the management and evaluation of communication and coordination practices among multi stakeholders in complex engineering projects in Pakistan. The methodology of this study is based on questionnaire to calculate the vested interest–impact index (ViII), Position (Pos), Attributes (A), Shareholder Impact Index (SII), Normalize score of SII and ranking of normalize score of SII. In addition, this study also used the Stakeholder Impact/Probability matrix. There are 44 questions asked from 132 respondents. The result reveal that different stakeholders showed interests in construction projects, however, every stakeholder had their own agenda and interest which create a conflict. Stakeholders' impact index and probability impact matrix approach for assessment of current practice and their requirements for coordination and communication have been used. Study also represents the class and position of stakeholders during both phases. As per results, land owners have high and positive impact on complex projects throughout the project life cycle followed by local community/residents, media, institutional forces and politicians. The politicians have highest positive impact on complex projects followed by consultant, main contractor and government agencies. Efficient communication and coordination is required with low impact stakeholders for minimizing their influence. It is observed that the high value of ViII will lead to higher value of SII and normalize score of project’s PP and EP. The top five stakeholders are clients, consultants, main contractors, sub-contractors and government agencies in project’s planning and execution phase. The shareholder impact analysis also provides suggestions to project managers in developing and evaluating the stakeholder management process. The proposed study is first approach towards communication and coordination management in construction. Overall, the results show that since there is no contractual binding between external stakeholders and project sponsors, they face the maximum communication gap. There is no proper mean to establish coordination and communication among external stakeholders throughout the project.